2009
DOI: 10.1002/app.30915
|View full text |Cite
|
Sign up to set email alerts
|

Radiation grafting of acrylic acid/N‐vinyl pyrrolidone binary mixture onto poly(ethylene terephthalate) fabric and growth of human mesenchymal stem cell

Abstract: Radiation grafting of acrylic acid (AA)/Nvinyl pyrrolidone (NVP) binary mixture onto poly(ethylene terephthalate) (PET) knittings was investigated by preirradiation technique. The influence of the grafting conditions, such as monomer composition, reaction temperature, and the effect of storage time with temperature after irradiation on the degree of grafting was determined. ATR-FTIR spectroscopy analysis of the grafted knittings confirmed the existence of amide group of NVP in the knittings. The concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 146 publications
(146 reference statements)
1
4
0
Order By: Relevance
“…This may be due to the deactivation of some of the radicals, thereby resulting in the decrease of grafting. Similar observation was observed by Gupta et al 42 in case of N-VPg-acrylamide. Initial increase in the degree of grafting with an increase in the monomer concentration is due to unhindered accessibility of the monomer to the primary radicals.…”
Section: Effect Of Monomer Content On the Percentage Of Graftingsupporting
confidence: 89%
“…This may be due to the deactivation of some of the radicals, thereby resulting in the decrease of grafting. Similar observation was observed by Gupta et al 42 in case of N-VPg-acrylamide. Initial increase in the degree of grafting with an increase in the monomer concentration is due to unhindered accessibility of the monomer to the primary radicals.…”
Section: Effect Of Monomer Content On the Percentage Of Graftingsupporting
confidence: 89%
“…[15] One of the monomers that are employed in the graft copolymerization of silk in that study, N-vinylpyrrolidone (NVP), was reported to be grafted onto many fiber/fabric surfaces except silk fiber in the literature, with a limited grafting yield (most often lower than 30%). [16][17][18][19] Except in a study published in the literature, the authors claimed that they reached more than 200% grafting yield of NVP onto the cotton fabric when they utilized microwave-assisted graft copolymerization using ammonium persulfate (APS) as an oxidant. [20] In the study, the amount of NVP was reported to be more than 5 mL, possibly leading to bulk poly(N-vinylpyrrolidone) (PVP or PNVP) formation.…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiation was successfully used for grafting vinyl polymers (e.g., PDMAEMA, poly(acrylic acid), and polyvinylpirrolidone) onto the surface of various kinds of polymer materials such as poly(ethylene therephtalate), poly(vinylidene fluoride), cellulose, polypropylene, etc. [15][16][17][18][19][20][21]. Here again, it is important to note that in the case of cellulose, it was mostly fibers, micro-, or nanocellulose, i.e., grafting vinyl polymers onto neat cellulose is predominantly carried out under heterogeneous conditions with a water-based dispersant [22][23][24].…”
Section: Introductionmentioning
confidence: 99%